The complex relationship between government and NGOs in international development cooperation: South Korea as an emerging donor country. (1st October 2016) - Lee, Sook Jong; Lee, Kyoung Sun
Abstract: The South Korean government has sought an active partnership with domestic NGOs in pursuing international development cooperation. Their partnership can be categorized in two ways. One, the more common type, is that NGOs work with government offices by participating in established programs. In the second type of partnership, NGOs take a more independent position when important policy agendas are determined and often push the government to move in certain directions. Vibrant Korean NGOs usually align with more liberal rules and norms of foreign aid governance and advocate for these to their own government. The relationship between the government and NGOs in the area of development cooperation is essentially a partnership, as technical expertise and overseas aid allocation move their interaction away from divisive domestic politics. We named this partnership a "complex relationship" in which both functional and critical interactions occur. Three different types of relations – supplementary, complementary, and sometimes adversarial – co-exist across four interactive areas: volunteering services, development project implementation, development education, and policy advocacy.